2020
DOI: 10.1111/jfbc.13391
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the combination ofCyperus rotundus,Crocus sativus,Piper nigrum,andBoswellia serrataon learning and memory deficit and oxidative damage in brain tissue of hypothyroid rats

Abstract: In the present study, the impact of a combination of four memory‐enhancer herbs on cognitive impairment and brain tissue oxidative damage due to hypothyroidism was evaluated. Propylthiouracil (PTU; 0.05%) was administrated in drinking water. Rats were treated with a combination of four herbal products (Cyperus rotundus, Crocus sativus, Piper nigrum, and Boswellia serrata) mixed with honey at two doses (640 and 1,280 mg/kg) or donepezil (0.5 mg/kg), for 6 weeks. Memory performance on the Morris water maze (MWM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…In addition, DNPWMP treatment significantly increased the cell viability against Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) -induced neurotoxicity compared to DNP and WMP treatment (by 23.0 and 13.7%, respectively). These results indicated that DNPWMP combination enhanced the cell viability in SH-SY5Y neuroblastoma cells-induced neurotoxicity by Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) compared to single treatment of DNP or WMP (Figure 1).…”
Section: Effect Of Wmp and Donepezil Hydrochloride (Dnp) Combination On Cell Viabilitymentioning
confidence: 91%
See 4 more Smart Citations
“…In addition, DNPWMP treatment significantly increased the cell viability against Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) -induced neurotoxicity compared to DNP and WMP treatment (by 23.0 and 13.7%, respectively). These results indicated that DNPWMP combination enhanced the cell viability in SH-SY5Y neuroblastoma cells-induced neurotoxicity by Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) compared to single treatment of DNP or WMP (Figure 1).…”
Section: Effect Of Wmp and Donepezil Hydrochloride (Dnp) Combination On Cell Viabilitymentioning
confidence: 91%
“…The combinational effect of WMP and DNP on cell viability of SH-SY5Y neuroblastoma cells was evaluated using MTT assay. Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) treatment significantly reduced the cell viability (by 36.0%) compared to vehicle treatment. Treatment of WMP or DNP plus WMP (DNPWMP) significantly alleviated the neurotoxicity induced by Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (by 19.9% and 36.4% in WMP and DNPWMP treatments, respectively) compared to Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) treatment.…”
Section: Effect Of Wmp and Donepezil Hydrochloride (Dnp) Combination On Cell Viabilitymentioning
confidence: 99%
See 3 more Smart Citations